Female-Owned Firms during the COVID-19 Crisis - Hyland, Marie; Karalashvili, Nona; Muzi, Silvia; Viganola, Domenico (World Bank, Washington, DC, 2021)
This brief use firm-level data collected between May 2020 and May 2021 in 41 countries, to provide descriptive evidence on the differential effect of the Coronavirus disease 2019 (COVID-19) crisis on female- and male-owned firms. Data suggest that while female-owned and male-owned businesses closed permanently at the same rates, female-owned firms were more likely to have temporarily closed during the crisis and to have closed for a longer duration. When able to stay in business, female-owned firms were more likely to experience a decrease in demand for their products or services and supply of intermediate inputs than male-owned firms. They also reduced the size of their workforce more than their male counterparts and were more likely to reduce hours worked. Finally, female-owned firms suffered deeper financial distress than male-owned firms. Nevertheless, female and male-owned firms show similar optimism of returning to normal levels of sales or workforce in the near future.